345 The effects of maternal nutrient restriction followed by re-alimentation on offspring growth and metabolism in sheep - Smith, Brandon I (J Anim Sci, 2019)
The duration and timing of inadequate maternal nutrition can have detrimental effects on metabolism and organogenesis in the offspring. Re-alimentation, a common management practice that involves feeding full nutrient requirements following a period of nutrient restriction, may reduce the negative impacts of maternal nutrient restriction. To determine the effects of maternal nutrient restriction and re-alimentation on offspring growth,48 primiparous ewes, confirmed pregnant with singletons, were fed a control diet consisting of100% NRC requirements (CON) starting on day25 of gestation. On day50 of gestation, ewes (n = 7) were euthanized and fetal liver, muscle, and blood samples were collected. The remaining animals were fed either CON or60% NRC requirements (RES). On day90 of gestation, a portion of ewes were euthanized (n = 7 per treatment) and fetal samples and weights were collected. Remaining ewes were maintained on the current diet (CON-CON, n = 6; RES-RES, n = 7) or switched to the alternative diet (CON-RES, RES-CON; n = 7/treatment). On day130 of gestation, all remaining ewes were euthanized. All fetal BW, liver, longissimus muscle, semitendinosus, and triceps brachii weights were determined for each day of gestation. Fetal BW’s were not different between treatment groups (P = 0.29; P = 0.83). Fetal liver weights decreased12.89% in RES-RES compared with CON-CON at day130 (P = 0.049), but were not different at day90 (P = 0.69). There was a tendency for decreased semitendinosus weight in RES group compared with CON at day90 (P = 0.055). Liver lipid droplet accumulation was analyzed for day90 and130 using histochemistry and an effect of maternal nutrition was not observed (P = 0.562). In summary, maternal nutrient restriction reduces offspring muscle and liver growth. To gain insight into the effects of maternal nutrient restriction and re-alimentation on liver development and metabolism, analysis of liver morphology, gene expression, and global metabolomics are needed. Supported by USDA-AFRI grant2016-67016-24884